CAR-T cell therapy and infection: a review. Issue 6 (3rd June 2021) - Bupha-Intr, Olivia; Haeusler, Gabrielle; Chee, Lynette; Thursky, Karin; Slavin, Monica; Teh, Benjamin
ABSTRACT: Introduction : Chimeric antigen receptor T-cell therapy (CAR-T cell therapy) is a novel immunotherapy with promising results in the treatment of relapsed or refractory B cell malignancies. Patients undergoing CAR-T cell therapy are at increased risk of infection due to prior immunosuppression, lymphodepleting chemotherapy, treatment of unique toxicities with tocilizumab and/or steroids, on-target effects of hypogammaglobulinaemia, and prolonged cytopenias. Areas covered : A narrative review of infections (PubMed, August 2020) occurring in patients undergoing CAR-T cell therapy is described, and the evidence for infection prevention strategies is presented. Expert commentary : The rapid adoption of CAR-T cell therapy into clinical practice presents many challenges for the diagnosis, management, and prevention of infection. Ongoing surveillance of the spectrum of infectious complications and effectiveness of prophylaxis is required to support safe and effective patient care.